Konformitas Teman Sebaya terhadap Perilaku Merokok Mahasiswa - Kharisma, Rr.Salwa Zasya Aura; Sary, Lolita; Aryawati, Wayan (UI Scholars Hub, 2023)
Background. Smoking behavior is a hazardous practice that continues to be normalized and trivialized by society. Factors contributing to smoking behavior include parental influence, personality factors, advertising influence, and peer conformity. Peer conformity holds the highest influence on smoking behavior, especially among teenagers, as adolescence is a period of self-discovery during which they explore various activities. Aim. To determine the relationship between peer conformity and smoking behavior. Method. Quantitative research of a cross-sectional design was conducted. The population consisted of 525 male students from the 2022 cohort, with a sample of 293 smoking students selected using purposive sampling technique. Data collection was carried out using a Google Form. Univariate data analysis was performed using frequency distribution, and bivariate analysis was conducted using the chi-square test. Results. There is a significant relationship between conformity with close friends (p-value 0.001 < 0.05) with an odds ratio (OR) of 20.476, a significant relationship between conformity with small group friends (p-value 0.003 < 0.05) with an OR of 0.397, and a significant relationship between conformity with organization group friends (p-value 0.002 < 0.05) with an OR of 0.422 concerning smoking behavior. There is no significant relationship between conformity with gang group friends (p-value 0.077 > 0.05) and large group friends (p-value 0.754 > 0.05) and student smoking behavior. Conclusion. The smoking behavior in students is caused by conformity with close friends, small group friends, and organization group friends